Prognosis and Risk Factors of Stroke After Thoracic Endovascular Aortic Repair for Stanford Type B Aortic Dissection - Zha, Zhengbiao; Pan, Youmin; Zheng, Zhi; Wei, Xiang (Frontiers in Cardiovascular Medicine, 2022)
Background: Stroke is a severe complication of patients with type B aortic dissection (TBAD) after thoracic endovascular aortic repair (TEVAR). Our aim is to identify predictors of stroke after TEVAR. Methods: From February 2016 to February 2019, 445 patients with TBAD who underwent TEVAR were retrospectively analysed. Univariate and multivariate analysis were performed to identify predictors of stroke after TEVAR. Results: The total incidence of stroke was 11.5%, with transient neurological dysfunction (TND) 10.6% and permanent neurological dysfunction (PND) 0.9%. The average age of the patients was 53.0±3.2 years and male/female ratio was 1.17. Univariate analysis suggested that age, BMI, diabetes mellitus, COPD, urgency of repair, type of anaesthesia and left subclavian artery (LSCA) processing were potential risk factors of stroke after TEVAR. Multiple logistic regression identified that LSCA coverage (OR=5.920, 95% CI: 2.077-16.878), diabetes mellitus (OR=3.036, 95% CI: 1.025-8.995), and general anaesthesia (OR=2.498, 95% CI: 1.002-6.229) were independent predictors of stroke after TEVAR. Conclusions: LSCA coverage, diabetes mellitus, and general anaesthesia were independent risk factors of stroke after TEVAR for TBAD.